2015
DOI: 10.1177/0002716214554758
|View full text |Cite
|
Sign up to set email alerts
|

Why People “Don’t Trust the Evidence”

Abstract: In this commentary, we embed the volume's contributions on public beliefs about science in a broader theoretical discussion of motivated political reasoning. The studies presented in the preceding section of the volume consistently find evidence for hyperskepticism toward scientific evidence among ideologues, no matter the domain or context-and this skepticism seems to be stronger among conservatives than liberals. here, we show that these patterns can be understood as part of a general tendency among individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(60 citation statements)
references
References 44 publications
3
56
0
1
Order By: Relevance
“…Our simpler, neutral polar-knowledge scale bypasses this limitation and thus offers a different window on biased assimilation. Biased assimilation occurs among people of all persuasions (Taber and Lodge 2006;Kraft et al 2015), but that does not mean it is equally prevalent. Table 3 identifies a large segment, almost half our respondents, who combine high self-assessed understanding of climate change with low factual knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our simpler, neutral polar-knowledge scale bypasses this limitation and thus offers a different window on biased assimilation. Biased assimilation occurs among people of all persuasions (Taber and Lodge 2006;Kraft et al 2015), but that does not mean it is equally prevalent. Table 3 identifies a large segment, almost half our respondents, who combine high self-assessed understanding of climate change with low factual knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Better educated individuals could be particularly effective in doing so, accounting for the widely observed information×politics interactions. Motivated skepticism (Taber and Lodge 2006;Kraft et al 2015), cultural cognition (Kahan et al 2011) and other theoretical concepts have similar themes of information acquisition filtered by worldview or pre-existing beliefs. Applied to polar regions, for example, we see some people rejecting scientific reports about melting Arctic sea ice, and eager to accept weakly founded claims of recovery.…”
Section: Climate Change Polar Facts and Perceptionsmentioning
confidence: 99%
“…26 Oko četiri petine članaka odnose se na klimu, dok se ostali članci odnose na poricanje znanosti u drugim pitanjima okoliša ili na općenitijoj razini. 27,28,29 Poricanje znanosti o klimi daleko je najrasprostranjeniji oblik poricanja znanosti, što predstavlja okosnicu opozicije prema ekologiji i znanosti o okolišu, posebno u Sjedinjenim Američkim Državama, ali i u određenoj mjeri u Velikoj Britaniji i Australiji. Nekoliko je skupina poricatelja znanstvenih činjenica o klimatskim promjenama, pri čemu jedna grupacija osporava da je došlo do znatnijeg zagrijavanja, a drugi dovode u pitanje njegovu antropogenu prirodu, često je pripisujući Sunčevim aktivnostima, dok treća grupa skeptika prihvaća antropogene klimatske promjene, ali poriče da će imati znatne (ne-2015.…”
Section: Globalno Zatopljenje -Analiza Recentnih Trendova I Parametaraunclassified
“…. [and] there is mounting evidence that the most politically sophisticated and knowledgeable among us are the most prone to the strongest bias'' [Kraft et al, 2015]. And scientists should not feel too smug about their supposed objectivity: studies have shown that scientific reviewers are also vulnerable to confirmation bias, tending to rate papers more highly when they confirm previously held beliefs [e.g., Mahoney, 1977;Koehler, 1993].…”
Section: Science In the Public Interestmentioning
confidence: 99%